In Situ Capture RT-qPCR: A New Simple and Sensitive Method to Detect Human Norovirus in Oysters - Zhou, Zhenhuan; Tian, Zhengan; Li, Qianqian; Tian, Peng; Wu, Qingping; Wang, Dapeng; Shi, Xianming (Frontiers in Microbiology, 2017)
Human noroviruses (HuNoVs) are the major cause worldwide for non-bacterial acute gastroenteritis. In this study, we applied a novel viral receptor mediated in situ capture RT-qPCR (ISC-RT-qPCR) to detect HuNoVs in oysters and compared with the traditional RT-qPCR method. Ten HuNoVs RT-PCR positive and 5 negative clinical samples from gastroenteritis patients were used to compare specificity and sensitivity of ISC-RT-qPCR against that of the RT-qPCR assay. ISC-RT-qPCR had at a one-log and a two-log increase in sensitivity over that of the RT-qPCR assay for genotype I (GI) and GII, respectively. Distributions of HuNoVs in oyster tissues were investigated in artificially inoculated oysters. GI HuNoVs could be detected in all tissues in inoculated oysters by both ISC-RT-qPCR and RT-qPCR. GII HuNoVs could only be detected in gills and digestive glands by both methods. The number of viral genomic copies (vgc) measured by ISC-RT-qPCR was comparable with RT-qPCR in the detection of GI and GII HuNoVs in inoculated oysters. Thirty-six oyster samples from local market were assayed for HuNoVs by both assays. More HuNoVs could be detected by ISC-RT-qPCR in retail oysters. The detection rates of GI HuNoVs in gills, digestive glands, and residual tissues were 33.3%, 25.0%, and 19.4% by ISC-RT-qPCR; and 5.6%, 11.1%, and 11.1% by RT-qPCR, respectively. The detection rates of GII HuNoVs in gills were 2.8% by ISC-RT-qPCR; no GII HuNoV was detected in these oysters by RT-qPCR. Overall, all results demonstrated that ISC-RT-qPCR is a promising method for detecting HuNoVs in oyster samples.